Ultrafast enhancement and optical control of magnetization in ferromagnet/semiconductor layered structures via superdiffusive spin transports. (September 2022) - Jiang, Tianran; Zhao, Xupeng; Chen, Zhifeng; You, Yongyong; Lai, Tianshu; Zhao, Jianhua
Abstract: While several mechanisms of ultrafast demagnetization were still being debated, a new superdiffusive spin transport (SST) was proposed as a new mechanism of ultrafast demagnetization in layered structures, and was demonstrated in ferromagnet/normal metal and ferromagnet/normal metal/ferromagnet layered structures. Transient magnetization enhancement in Fe layer was observed as the evidence of SST in a Ni/Ru/Fe layered structure when the Ni layer was photo-excited. However, it was not observed repeatedly elsewhere. Here, we explore possible SST in a new ferromagnet/semiconductor layered structure without magnetic couplings, and observe transient magnetization enhancement in directly photo-excited L 10 -MnGa ferromagnetic layer of a L 10 -MnGa/GaAs layered structure, being very convincing evidence of SST because the magnetization enhancement occurred impossibly in a sole photo-excited L 10 -MnGa layer if there were no SST from GaAs layer. It is more fascinating that we fulfill ultrafast optical manipulations of transient magnetization in L 10 -MnGa layer using circularly polarized pump pulses (CPPP). Right-handed CPPP can enhance transient magnetization extremely over linearly polarized pump pulses, while left-handed CPPP can weaken one vastly. A modified three-temperature model is developed to take account of SST effect and is used to reproduce our experimental results well. Our results exhibit high efficient and ultrafast bidirectional magnetic modulations in ferromagnet/semiconductor hybrid structures which have potential applications in ultrafast magneto-optical modulations and optical manipulations of ferromagnet/semiconductor hybrid spintronic devices. Graphical abstract: Image 1 Highlights: A new ferromagnet/semiconductor layered structure, MnGa/GaAs bilayer sample constructed. Femtosecond laser-induced magnetization dynamics studied by MOKE. Observations of transient magnetization enhancement in MnGa layer, very convincing evidence as superdiffusive spin transport. First ultrafast optical control of magnetization in this layered structures via superdiffusive spin transports is fulfilled. A modified three temperature model is developed to simulate the superdiffusive spin transport.